Culture: management and financing in the Russian digital reality - O. V. Kryshtanovskaya; I. A. Lavrov; N. S. Evsegneeva (Цифровая социология)
The state, by virtue of its nature, is capable of controlling and regulating all spheres of society. The main instrument of this regulation is the ability to redistribute resources between different spheres of life. Russia, in the era of new global challenges in the conditions of fierce information competition, needs to pay special attention to the cultural sphere of society. It is the preservation and transmission of cultural values, norms and experience to new generations that are able to ensure the unity of multinational people in turbulent circumstances. However, due to numerous factors, the cultural sector, receives insufficient state support and funding. In modern realities, in addition to economic problems, the sphere of culture is experiencing new difficulties associated with the digitalization of society. The article presents the results of the research, in the course of which the all-Russian expert survey was conducted. The experts gave their opinions on the most urgent problems in the sphere of culture, which were subsequently analysed. The most acute issue, according to the majority of experts, is the underfunding of the cultural sphere, which leads to significant consequences: unequal participation of citizens in cultural life, use of cultural institutions, limited access to cultural values; personnel stagnation in this sphere. In addition, the sphere of culture is subject to the processes of politicization and commercialization, which slows down its development and reduces the overall level, which has a negative impact on society. Experts state that cultural reforms aimed at modernization and the revision of cultural policy are necessary in the sphere of culture. Such changes are possible only with the adoption of a new law “on culture”, which would renew public administration in this sphere and ensure the progressive and systematic growth of the cultural level of the population.